2022
DOI: 10.1111/plb.13397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postharvest hydrogen sulphide on lignification and biochemical markers of pointed gourd

Abstract: Hydrogen sulphide (H2S) has emerged as a gasotransmitter molecule that modulates several physiological functions in plants, specially, different biotic and abiotic stresses. Pointed gourd (PG) fruits start losing their soft texture and appealing colour within 2–3 days of harvest, resulting in poor marketability and shelf life. Here, the effect of exogenous H2S (1 and 2 mm) application on lignification and other biochemical markers linked to ripening, shelf‐life and edible quality of PG was assessed during cold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…Recently, exogenous application of H 2 S on the activity of various biochemical markers linked to fruit ripening in the fruits of banana and pointed gourd in the post-harvest stage was analyzed to detect their quality and shelf life. They unraveled that exogenous application of H 2 S significantly lowered membrane damage, lignification, and chlorophyll loss and correspondingly maintained higher PAL and PPO activity, thereby increasing the shelf life of the fruits without compromising their quality and extending their marketing duration [ 156 , 157 ].…”
Section: Potential Biotechnological Application In Agriculturementioning
confidence: 99%
“…Recently, exogenous application of H 2 S on the activity of various biochemical markers linked to fruit ripening in the fruits of banana and pointed gourd in the post-harvest stage was analyzed to detect their quality and shelf life. They unraveled that exogenous application of H 2 S significantly lowered membrane damage, lignification, and chlorophyll loss and correspondingly maintained higher PAL and PPO activity, thereby increasing the shelf life of the fruits without compromising their quality and extending their marketing duration [ 156 , 157 ].…”
Section: Potential Biotechnological Application In Agriculturementioning
confidence: 99%
“…Siddiqui et al (2022) reported that H 2 S significantly protects the quality of banana fruits after harvest by inhibiting oxidative damage, rapid ripening and senescence; H 2 S delays chlorophyll degradation and suppresses ethylene and CO 2 production. Also, the study of Lata et al (2022) revealed that postharvest exogenous H 2 S application markedly delays yellowing and chlorophyll loss, improves phenolics content and antioxidant activity and reduces lignification and membrane permeability of guard cells during cold and ambient storage.…”
Section: Emerging Role Of Hydrogen Sulphide As a Signalling Molecule ...mentioning
confidence: 99%
“…Also, the study of Lata et al . (2022) revealed that postharvest exogenous H 2 S application markedly delays yellowing and chlorophyll loss, improves phenolics content and antioxidant activity and reduces lignification and membrane permeability of guard cells during cold and ambient storage.…”
mentioning
confidence: 99%
“…A lignification process increases the firmness of postharvest fruits and vegetables, and this process is directly caused by lignin biosynthesis [10]. Phenylpropanoid metabolism takes on great significance in the postharvest lignification of fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%